KORELASI PEMEGANG HAK ATAS TANAH DAN PENGENAAN BPHTB DALAM PROSES PERALIHAN HAK KARENA PEWARISAN DI KANTOR PERTANAHAN - Iskandar, Tudi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This study aims to determine the process of transfer of rights due to inheritance at the Land Office and the correlation of right holders who are also heirs with the imposition of BPHTB. This study concludes that the transfer of land rights due to inheritance on certificates written in the singular where there is the role of a married couple in the acquisition of the land, the subject who will receive the land rights will be burdened with the obligation to pay BPHTB in full and round. On the other hand, in the case of a transfer of rights on a plurality of certificates, the subject who receives the land title will be liable to pay BPHTB in full and in full, resulting in a difference in the calculation of the BPHTB charge. The difference in the calculation of BPHTB will ease the payment obligations of the heirs who also play a role in the acquisition of land rights.